Hadith #4847 - Sahih Muslim - Abu Tha'laba al-Khushni (Sahih Muslim)
I came to Allah’s Messenger (ﷺ) and said: Allah’s Messenger, we are in the land of the People of the Book, (so) we eat in their utensils, and (live) in a hunting region. where I hunt with, the help of my bow, and hunt with my trained dog, or with my dog which is not trained. So inform me what is lawful (Halal) for us out of that. He (the Holy Prophet) said: Regarding what you have mentioned of the fact that you live in the land belonging to the People of the Book and so you eat in their ut
Grade: Sahih

Hadith #4849 - Sahih Muslim - Abu Tha'laba al-Khushni (Sahih Muslim)
If you shoot with your arrow and (the game) goes out of your sight and you find it (later on), then eat that if it has not gone rotten.
Grade: Sahih

Hadith #4850 - Sahih Muslim - Abu Tha'laba al-Khushni (Sahih Muslim)
Eat it, provided it has not gone rotten.
Grade: Sahih

Hadith #4851 - Sahih Muslim - Abu Tha'laba al-Khushni (Sahih Muslim)
He (the Holy Prophet) said in regard to the game killed by (a trained) dog: Eat after three days provided it has not gone rotten.
Grade: Sahih

Hadith #4852 - Sahih Muslim - Abu Tha'laba al-Khushni (Sahih Muslim)
We did not bear of it until we came to Syria.
Grade: Sahih

Hadith #4853 - Sahih Muslim - Abu Tha'laba al-Khushni (Sahih Muslim)
I did not bear of this from our ‘Ulama’ in the Hijaz, until Abu Idris narrated that to me and he was one of the jurists of Syria.
Grade: Sahih